Development of Authentic Assessment Instrument to Measure Students Critical Thinking Skills on Temperature and Heat Subject Matter at SMAN 2 Medan - Lioni Widya Sonata Tampubolon; Yeni Megalina (Physics Education Research Journal, 2025)
This research aims to develop an authentic assessment instrument in the form of cause-and-effect multiple-choice questions to measure students' critical thinking skills on the topic of temperature and heat at SMAN 2 Medan. The study is motivated by the limited implementation of authentic assessments in physics learning and the lack of students’ engagement in context-based evaluations that foster critical thinking. The research employed a Research and Development (R&D) method using the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. Validation was conducted by two university lecturers and one physics teacher, followed by small and large group trials, and item analysis was performed to evaluate validity, reliability, difficulty level, discrimination index, and distractor effectiveness. Teacher responses were also gathered to assess the feasibility and practicality of the instrument. The results indicate that the developed instrument met validity and reliability criteria, with most items demonstrating appropriate levels of difficulty and discrimination. Teachers responded positively, stating that the instrument was clear, practical, and aligned with the needs of physics learning under the Merdeka Curriculum. Based on the findings of the study, it can be concluded that the authentic assessment instrument in the form of cause-and-effect items is feasible and effective in measuring students' critical thinking skills on the topic of temperature and heat. The implication is that this instrument can serve as an alternative evaluation tool for teachers to assess students’ understanding in a deeper and more contextual manner while promoting active engagement in critical thinking.